Atrial Fibrillation Development Risk Associated with Metabolic Syndrome - Alfata, Fandy Hazzy; Rizal, Ardian; Rohman, Mohammad Saifur; Rahimah, Anna Fuji (Universitas Brawijaya, 2023)
Even in the absence of antecedent myocardial infarction or congestive heart failure, atrial fibrillation (AF) is the most frequent arrhythmia seen in daily practice. There are several important predisposing factors for the initiationof AF, including growing older, being a man, being female, having high blood pressure, and having cardiac and noncardiac illnesses. Metabolic syndrome (MS) contributes to the progression of AF through its impact on the atrial substrate. MS involves metabolic risk factors that increase the likelihood of atherosclerotic cardiovascular disease and type 2 diabetes. Insulin resistance plays a significant role in MS pathophysiology, leading to glucose and lipid metabolism dysregulation, increased inflammation, and neurohormonal activation. These processes contribute to the development of hypertension, a major risk factor for AF. Atrial remodeling, including electrical and structural changes, is a common substrate for AF, and MS components further contribute to this remodeling.Hypertension, a key feature of MS, is associated with structural, contractile, and electrical remodeling in the atria, increasing the risk of AF. The renin-angiotensin-aldosterone system, implicated in hypertension regulation, alsoinfluences the pathophysiology of AF through fibrosis, ion channel alterations, oxidative stress, and inflammation. Understanding the intricate interplay between MS and AF can provide insights into therapeutic strategies for managing these conditions and reducing cardiovascular risks.